Contextualization of the Umminess of the Prophet Muhammad in the Qur’an: an Analysis of the Burhani Epistemology of Muhammad Abed Al-Jabiri - Abd. Basid; Achmad Khudori Soleh (JURNAL AT-TURAS, 2024)
Prophet Muhammad was a perfect person in all things. His character, attitude, and intellectuality cannot be determined by anyone. Because of his profession, he received the title of Al-Amin, because of his morality he was known as a person with noble character and an example, and because of his intelligence, he could master language intelligence, arithmetic, memorization, visual intelligence, vision intelligence, and intelligence in solving problems. But behind all that, Prophet Muhammad was known as an ummi, meaning he could not read and write. Is a perfect person worthy of having an ummi personality? This study aims to explain the concept of the ummi of the Prophet Muhammad by observing the epistemology of Burhani Muhammad Abed Al-Jabiri. It is hoped that later it can produce a conclusion that successfully recontextualizes the meaning of ummi so that the existence of the Prophet Muhammad is truly very important. His greatness and glory can factually fulfill the four mandatory characteristics of the apostle. The method used in this study is a qualitative approach that is library-based and the data analysis used is descriptive. The results of this study indicate that the existence of the Prophet Muhammad as an ummi is that he did not know and understand the contents of the Bible at all. However, the revelation of the Qur'an that he received had many similarities in content, such as previous stories. The results of this conclusion then became a re-contextualization of the meaning of ummi, because if until now ummi is still interpreted as illiterate, it does not change that the Prophet Muhammad was stupid and backward and contradicts one of the mandatory characteristics that must be possessed by a Messenger, namely fathanah (intelligent).